(untitled) (The International Research Journal of Management Science, 2019)
Background: Human resource is dynamic and complex ever because of changes in local, regional and global dimensions. Managing people for optimal use of their competencies for organizational purpose has no options. Employee motivation and employee turnover is being the central issue in the modern organizations, corporate movement of competent people is being the regular corporate news in business arena. Human capital management (HCM) helps them to be satisfied and being positive to their work and the organization. It helps organization to cope with turnover challenge and deviant workplace behavior. Employee motivation, satisfaction, job burnout, turnover are being common challenges to the management. To cope with such challenges, organizations should have strategic focus on human capital management. Objectives: This study aims to explore the situation of human capital management in Nepali insurance companies and the employee’s satisfaction from human capital management. The study also aims to examine the association between satisfaction from HCM and workplace behavior. To examine the gender influence on workplace behavior of the employees created by HCM. Methods: This study was conducted with correlational research design. Primary data for each variable was collected from 402 employees of different seven life insurance companies having at least five years of business experience. To observe the current HCM practices, 3-Point statements were asked. Structured questionnaire with 5-Point Likert Scale was used to collect responses on satisfaction from HCM and the satisfaction towards positive workplace behavior. Descriptive statistics, Pearson correlation, and independent sample t-tests were used to examine the objectives. Result: Results of the study revealed that Nepali insurance companies have maintained human capital management causing employee satisfaction. Employees have reported that they have positive workplace behavior. Female employees have more positive workplace behavior of employees. Employee’s satisfaction from HCM is obtained having positive relationship with workplace behavior. Conclusion: Nepali insurance companies have satisfactory HCM effective to motivate their employees. Employee’s satisfaction leads for positive workplace behavior. There is no gender difference in satisfaction on HCM while female have more positive workplace behavior in comparison to their male counterparts. Implications: To cope with intense competition among the competitors in Nepali insurance industry, this study provides strong evidence to focus on HCM and positive workplace behavior.